RETRACTED ARTICLE: MiR-142-3p targeting NUCKS1 inhibits proliferation and invasion of pancreatic cancer cells. Issue 1 (1st January 2020) - Zhu, Kexiang; Zhang, Zhengcong; Zhang, Hui; Wang, Zhengfeng; Wang, Fanghong
Abstract: We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article: Kexiang Zhu, Zhengcong Zhang, Hui Zhang, Zhengfeng Wang & Fanghong Wang (2020) MiR-142-3p targeting NUCKS1 inhibits proliferation and invasion of pancreatic cancer cells. Artificial Cells, Nanomedicine, and Biotechnology, 48(1), 415–424, DOI: 10.1080/21691401.2019.1652629 Since publication, concerns have been raised about the integrity of the data in the article. In addition, during the course of our investigation it has come to our attention that the authorship list and affiliations for this manuscript were significantly changed after the article was accepted. We have contacted the corresponding author for an explanation, but we have not received a response. As determining authorship is core to the integrity of published work, and we have also been unable to verify the original data, we are retracting the article. The corresponding author listed in this publication has been notified. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.